Effect of rhizobacteria on onion seeds and seedlings - Harthmann, Oscar Emílio Ludtke (2020)
This study assesses the effects of rhizobacteria on the germination and growth of onion seedlings. Tenisolates from treatments of Pseudomonas and Bacillus in seeds were used. The effect of the microbiolization in seedswas assessed in laboratories and fields. There was an influence of rhizobacteria on the germination and development of the onion seedlings in laboratory. The rhizobacteria which promoted better germination and development werethose of the seedlings Bacillus megaterium, isolated W7 and W19, and Bacillus cereus UFV40. The treatments with rhizobacteria did not promote significant effects either on the growth of seedlings or on the reduction of the Botrytis squamosa disease in the fields phase.